2019
DOI: 10.1017/s0033291719002265
|View full text |Cite
|
Sign up to set email alerts
|

Toward a paradigm shift in treatment and research of mental disorders

Abstract: Mental disorders are common and represent a significant and worldwide public health concern (Smith, 2011; Vigo et al., 2016; Patel et al., 2018). The global burden of disease due to mental illness accounts for 21-32% of years lived with disability and 7-13% of disability-adjusted life-years (Vigo et al., 2016). The Lancet commission on global mental health and sustainable development just recently estimated a loss of US$16 trillion to the global economy due to mental disorders in the period 2010-2030 (Patel et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 99 publications
(180 reference statements)
1
29
0
1
Order By: Relevance
“…The small effect sizes in the present study were anticipated because of the short treatment period for adolescents experiencing complex MH problems. The results are in line with a previous finding, which showed that efficacy of psychotherapy when compared to TAU is limited with an effect size of 0.30 or below (46). However, according to a systematic review of adolescent depression (47), most studies used clinicians' measures of symptom change, while patients' and parents' perspectives, as well as their personal growth, interpersonal relationships, and school performance were not assessed.…”
Section: Discussionsupporting
confidence: 89%
“…The small effect sizes in the present study were anticipated because of the short treatment period for adolescents experiencing complex MH problems. The results are in line with a previous finding, which showed that efficacy of psychotherapy when compared to TAU is limited with an effect size of 0.30 or below (46). However, according to a systematic review of adolescent depression (47), most studies used clinicians' measures of symptom change, while patients' and parents' perspectives, as well as their personal growth, interpersonal relationships, and school performance were not assessed.…”
Section: Discussionsupporting
confidence: 89%
“…Interoception is now recognized to be a fundamental mechanism underlying motivation, emotion, social cognition and selfawareness (Tsakiris and Critchley, 2016), and interoceptive awareness is associated with individual differences in one's ability to inhibit behavior (Rae et al, 2019). There is also increasing multidisciplinary evidence that interoception is predictably impaired in mental health conditions and should be considered as a transdiagnostic therapeutic target (Khalsa et al, 2018), especially given that psychiatric patients do not completely remit and at least 50% do not respond to standard treatments (Leichsenring et al, 2019). Accordingly, therapy approaches that emphasize interoceptive mechanisms are important to consider and are likely to be central to future developments in clinical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the core of DBT is to help people build four essential skills: mindfulness, distress tolerance, interpersonal effectiveness, and emotional regulation. Recently these new approaches have been used to treat patients with BD [187]; [188]; [189]. Thus, through this research, our group aims to select patients for a future study about DBT, allowing them to develop new behaviors and skills.…”
Section: Discussionmentioning
confidence: 99%